การศึกษาการใช้โปรแกรมสัมพันธภาพบำบัดต่อพฤติกรรมการดูแลตนเองด้านสุขภาพจิตของผู้ที่พยายามฆ่าตัวตาย โรงพยาบาลอ่างทอง - ธนพร วิชชุเวสคามินทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The objective of this independent study project was to compare the psychological self-care behaviors of suicidal attempters before and after their participation in a therapeutic relationship program. The sample consisted of twenty persons who had attempted suicide. The instruments used in this study were: 1) Therapeutic relationship program, 2) The Psychological Self-Care Behaviors Measurement developed by Jintana Yunibhand (B.E 254B). Cronbach’s alpha reliability coefficient for the instrument was .03. Statistical used for data analysis were paired t-test. Major findings were as follows. The psychological self-care behaviors of suicide attempters after using the therapeutic relationship program, were significantly higher than before the program, p = .05.